Understanding the Process of Medical Referral: Part 6: Closure, compliance, and outcome - Muzzin, Linda J. (1992)
In this, the concluding article of a six-part series on a longitudinal study of 50 referrals from family physicians in Ontario and Manitoba, the end of the referral process and responsibility for it are examined. Referral seemed to function as a process that, sometimes inappropriately, restored faith or held out hope that medical solutions could be found for difficult, chronic problems. Outcomes were linked to patient agendas and expectations.